ANALYSIS THE INFLUENCE OF WORK CULTURE ON THE QUALITY OF SERVICE OF EMPLOYEES AT BUTON DISTRICT GENERAL HOSPITAL - Syahrabudin Husein Enala; Syahruddin Syahruddin; Muhammad Novan Prasetya (Nusantara Hasana Journal, 2022)
The purpose of this study was to analyze the influence of work culture on the quality of employee services at the Buton Regency Regional Hospital. The problem contained in this study is the phenomenon that occurs at the Buton Regency Hospital that officers do not serve patients well, including favoritism in services, especially patients who are known to be handled quickly, the unfriendly attitude shown by the officers. The method uses the correlational method, which is to be able to see the magnitude of the influence of free variables on the bound variables. The free variable is organizational culture, while the bound variable is the quality of public services. The techniques used are survey and interview techniques, survey techniques by distributing questionnaires to 30 employees of Buton district hospital. Meanwhile, the interview was addressed to the Director of the Buton Regency Regional General Hospital and the Informant comparing 1 patient, and 1 patient family to compare the data on the quality of public services from the District Hospital as a servant and the Patient and his family as recipients of Public services in this case served. The results showed that based on the results of the analysis obtained thitung (4,602) > ttabel (1,71) maka H0 rejected. This means that work culture has a real effect on the variable quality of service. So far, research related to work culture has only focused on government or village institutions, and measured by employee performance, even if it is at the hospital, it only focuses on measuring performance, not the quality of public services. Meanwhile, excellence in this study of work culture is measured by the quality of public services.